RESEARCH METHODS OF WATER PURIFICATION FROM POLLUTION WITH PETROLEUM AND PETROLEUM PRODUCTS - Rizaev, Abdumalik (International Journal of Psychosocial Rehabilitation, 2020)
The article deals with the currently existing methods of water purification from petroleum and petroleum products, as well as analysis of the most popular ways to clean up the application of new technologies. The article briefly describes the technology of each method, as well as its main strengths and weaknesses, in particular, the use and quality of water treatment.